Analisis Pendapatan dan Kelayakan Usahatani Kecipir (Psophocarpus tertagonolobus L.) di Bukit Kor Terengganu Malaysia - Ramadan, Fuji Surya; Rangkuti, Khairunnisa (Universitas Medan Area, 2024)
In Asia, the winged bean is known by various names, such as bottle bean (Malaysia), dragon bean (Vietnam), mountain bean (Laos, Thailand), and winged bean (Indonesia). Winged bean is a tropical plant that is quite adaptive to grow in the lowlands and highlands and also in dry environmental conditions. Winged bean is a plant that is quite popular and much loved by the people of Malaysia. Winged beans are usually consumed as a substitute for vegetables. Demand for winged beans is expected to continue to increase so that it has the opportunity to become a very profitable farming business. This research aims to analyze the income and feasibility of winged bean farming in Bukit Kor Terengganu, Malaysia. The method used is descriptive. The sampling method uses saturated samples. The research was conducted in Bukit Kor with 15 farmer respondents. From winged bean farming with a land area of 1 ha, a winged bean production of 20 tons/MT is obtained with a production cost of IDR 45,651,000/MT. The results of research on production costs incurred for Kecipir farming are land management costs of Rp. 1,120,000, depreciation costs of Rp. 7,683,200, seed costs Rp. 4,320,000, Fertilizer costs Rp. 6,928,000, pesticide costs Rp. 720,000, labor costs Rp. 24,400.00. So, these results show that winged bean farming in Bukit Kor is profitable with a farmer income of IDR 1,105,348,800/MT. The B/C ratio value obtained is 25, meaning that winged bean farming in Bukit Kor Terengganu, Malaysia is profitable and suitable for farming. Economic feasibility obtained from farming. Harvesting winged beans can be done regularly once a week because this plant grows continuously until it is 5 months old. This plant has great potential to be developed as a substitute food for soybeans because its productivity is higher than other legume seeds, reaching around 2.58-8.94 tonnes/hectare.